Source Monitoring and Executive Function in 2.5- to 3-Year-Olds. Issue 3 (26th May 2016) - Hala, Suzanne; McKay, Lee-Ann; Brown, Alisha M. B.; San Juan, Valerie
Abstract : Hala, Brown, McKay, and San Juan (2013) found that children as young as 2.5 years of age demonstrated high levels of accuracy when asked to recall whether they or the experimenter had carried out a particular action. In the research reported here, we examined the relation of early-emerging source monitoring to executive function abilities. Participants were children aged 2.5- to 3-years old. For the source-monitoring procedure, we used the Hala et al. (2013) task in which children and the experimenter took turns placing a total of 20 items on a model farm (encoding phase). For the source memory test, children were asked who had placed each item (retrieval phase). Executive function measures included assessments of working memory, delay-inhibitory control, and conflict-inhibitory control. The main finding was that inhibitory control measures were significantly related to performance on the source-monitoring task. This relation held for the conflict-inhibitory control measures even when controlling for age and vocabulary. The findings of this research suggest that even at the early age of 2.5 years, development of executive control is linked to the emergence of source-monitoring ability.